Consider the following function.
Place the steps for finding f(x) in the correct order.
![Consider the following function Place the steps for finding fx in the correct order class=](https://us-static.z-dn.net/files/dfa/7c1f92d01b4bfa37779fabe8813a0040.jpg)
Answer:
[tex]\frac{x-7}{4} =f^{-1}( x)[/tex]
Step-by-step explanation:
→ Replace f(x) with y
y = 4x + 7
→ Minus 7 from both sides
y - 7 = 4x
→ Divide both sides by 4
[tex]\frac{y-7}{4} =x[/tex]
→ Replace y's with f⁻¹(x)
[tex]\frac{x-7}{4} =f^{-1}( x)[/tex]